ATTITUDE OF UNDERGRADUATESTUDENTS TOWARDS MORALVALUES –A CASE STUDYOFMORIGAON DISTRICT OF ASSAM - Nazma Begum; Tribeni Saikia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Education in its general sense means, modification of behaviour through knowledge, values,socially acceptable habits etc. It is not only the way for gaining the degree for economic status, but also earning and living a peaceful life in the society, with the knowledge to differ between right or wrong and good or bad. Students are the key maker of the society. A morally good student can make the society a good one. So, a positive attitude of undergraduate students towards moral values is a necessity of life. A value- based education is very much necessary to teach the students about the virtues and the strategies for inculcating the moral values. This research aims to find out the attitude of undergraduate students towards moral values of Morigaon District of Assam. In this case, the parents and the teacher have to play an important role to encourage the students to make a positive attitudetowards moral values. The sample size is selected through sampling method from the nine-degree colleges of the District. A self-made questionnaire is used to collect the primary data from the students. The result shows that majority of the students, that 50% have high positive attitude, 30% students have moderate positive attitude and 20% studentspoor or a little bit negative attitude towards moral values. The results concluded that moral education must be imparted in the collegesthrough proper strategies by the teacher and by the parents at home.